An experiment in knowledge co-creation on the subsistence entrepreneurial ecosystem of metropolitan La Paz, Bolivia - Gover Barja Daza (Accountancy & Bedrijfskunde, 2020)
The Ecosistema del Emprendedor por Subsistencia Pace\~no, in Spanish, is a collection of books produced by the Bolivian Catholic University, with the active participation of graduating students involved in fieldwork research on a common topic of interest. Subsistence entrepreneurship is an important issue in a developing country context like Bolivia where it has not been studied from its ecosystem perspective. The collection concentrates mostly on the metropolitan area of La Paz. This article reviews the knowledge co-creation experiment among graduating students from different careers and their professors in studying and analyzing the La Paz's subsistence entrepreneurial ecosystem under conditions of research constraints.
Keywords: 650; Subsistence entrepreneurs; Social entrepreneurial ecosystems; Research experiments; Knowledge co-creation